Rebalancing growth in Asia: economic dimensions for China - "Arora, Vivek (ed.);Cardarelli, Roberto (ed.)" (New Delhi, 2010)
About the Book: Rebalancing Growth In Asia: Economic Dimensions for China "The call for rebalancing growth is primarily motivated by the experience of some Asian economies, especially that of China. No discussion could be deep or meaningful without careful considerations of data, theory, or international experience. No one has given more thought to this topic than the IMF staff. for any one interested in this subject, this book is a valuable source of the latest research that represents the best from the IMF."-Shang-Jin Wei Director of the Jerome A. Chazen Institute of International Business, N.T. Wang Professor of Chinese Business and Economy, and Professor of Finance and Economics, Columbia University
Keywords: Economic development-Asia